2014
DOI: 10.1177/039463201402700412
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TLR4 and CD14 Polymorphisms in the Pathogenesis of Respiratory Syncytial Virus Bronchiolitis in Greek Infants

Abstract: Clinical manifestations of respiratory syncytial virus (RSV) infection vary from minimal disease to severe acute bronchiolitis. The structural complex of TLR4/CD14 participates in the virus recognition as a component of natural immune response. Genetic variations of TLR4/CD14 may explain great variations in disease severity. The aim of this study was to investigate the possible role of polymorphisms of TLR4, Asp299Gly and Thr399Ile and CD14, C-159T and C-550T in the development of RSV bronchiolitis. Our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
0
26
1
Order By: Relevance
“…The main characteristics of all these studies are listed in Table . The genotype distributions of all 13 studies in the control groups conformed to the HWE except for one reported by Goutaki et al . (Table ).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The main characteristics of all these studies are listed in Table . The genotype distributions of all 13 studies in the control groups conformed to the HWE except for one reported by Goutaki et al . (Table ).…”
Section: Resultsmentioning
confidence: 62%
“…In this meta‐analysis, a total of six studies involving 1009 cases and 1348 controls were included to investigate the association between TLR4 Asp299Gly polymorphism and the risk of severe RSV infection (as shown in Table ). The meta‐analysis showed no substantial heterogeneity among studies in five genetic models (I 2 < 50%); thus, the fixed‐effect model was used to calculate the pooled ORs of these models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of HBoV1 not only could assist in the medical management of the patient but also contribute to surveillance of respiratory viruses, since the increased frequency of cases in the cold months ( Figure 1) accompanies the seasonal peak of other respiratory viruses such as RSV and FLU [45,46]. Recurrent episodes of LRTI might indicate a special susceptibility to respiratory infections and pathogens such as RSV or FLU can cause a severe illness depending on genetic risk factors that turn the host more vulnerable [47,48]. Therefore, patients with first-episode LRTI were compared to patients who had previous episodes of LRTI and hospitalization (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Two nonsynonymous SNPs in the TLR4 gene (D299G and T399I) and −550C/T variation in the CD14 gene have been implicated with RSV infection due to their mediate on different responses to infection . Some studies supported a positive association between these SNPs and severe RSV bronchiolitis, while others could not replicate this association . However, in a meta‐analysis, Zhou et al reported that all of these polymorphisms are not associated with the risk of severe RSV infection .…”
Section: Introductionmentioning
confidence: 99%